High Temperature Testing of NMC/Graphite Cells for Rapid Cell Performance Screening and Studies of Electrolyte Degradation. Issue 4 (1st April 2022) - Taskovic, T.; Eldesoky, A.; Song, Wentao; Bauer, M.; Dahn, J. R.
Abstract : LiNi0.5 Mn0.3 Co0.2 O2 /graphite cells with two different electrolytes underwent charge-discharge cycling at 70 °C. The 70 °C condition reduced the time it took for cells to lose significant capacity. Studies of the changes to the electrolyte after cycling by gas chromatography/mass spectrometry (GC/MS) and by Nuclear Magnetic Resonance spectroscopy (NMR) suggest that the same processes which cause cell failure and electrolyte degradation at 40 °C and 55 °C occur at 70 °C, only at an accelerated rate. Transition metal dissolution from the positive electrode was tracked using X-ray fluorescence studies of the negative electrode after testing. Based on the confidence obtained that the same degradation processes were occurring; advanced graphites were screened in NMC811/graphite cells at 70 °C. Differences in cell lifetime were apparent in weeks at 70 °C while the same differences took much longer to observe at 40 °C. It is our opinion that elevated temperature testing of Li-ion cells at 70 °C is a viable rapid screening technique for advanced electrolytes and advanced electrode materials.